Práticas e crenças parentais e comportamento de crianças nascidas pré-termo de muito baixo peso - Silveira, Jussânia Moraes Martins Aleixo da [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Due to significant technical and technological advances in neonatology, the survival rate of premature babies and babies having very low birth weight increased. Besides the post-discharge care, the importance of further investigation concerning the behavioral aspects of preterm born children, associated with the study of the influences of educational practices and parental beliefs is highlighted. The aim of this study was to describe and compare the educational practices and beliefs about the development of preterm babies parents (37 weeks) and babies with very low birth weight (1.500g) with parents of children born at term (most children born or equal to 37 weeks) of both sexes, age 22-43 months. Besides describing and comparing behavior problems in the same group we finally related educational practices and beliefs about parents development of this population. The results showed that mothers from both groups cared and encouraged their children, but the Preterm Group, stimulated more than they needed, pointing to a possible failure of the early stimulation program that they attended. Moreover, children GPT, according to reports from their mothers, had more behavior problems than children born at term. It was also observed correlation between educational practices and beliefs and behavior problems. However, the best the practices the more behavior problems

Due to significant technical and technological advances in neonatology, the survival rate of premature babies and babies having very low birth weight have increased. Besides the post-discharge care, the importance of further investigation concerning the behavioral aspects of preterm born children, associated with the study of the influences of educational practices and parental beliefs is highlighted. The aim of this study was to describe and compare the educational practices and beliefs about the development of preterm babies parents (37 weeks) and babies with very low birth weigth (1.500g) with parents of children born at term (most children born or equal to 37 weeks) of both sexes, age 22-43 months. Besides describing and comparing behavior problems in the same group we finally related educational practices and beliefs about the parents development of this population. The results showed that mothers from both groups cared and encouraged their children, but the Preterm Group, stimulated more than they needed, poiting to a possible failure of the early stimulation program that they attended. Moreover, children GPT, according to reports from their mothers, had more behavior problems than children born at term. It was also observed correlation between educational practices and beliefs and behavior problems. However, the best the practices the more behavior problems
Practices and parental beliefs and behavior of children born preterm very low birth weight
Keywords: Neonatologia; Recem-nascidos - Peso baixo; Psicologia infantil; Avaliação de comportamento; Responsabilidade dos pais; Neonatology